Starch Based Antioxidant Active Packaging - Mukhtalifah, Sukhufum
Active packaging promotes shelf life extension and quality control of a food product. Unfortunately, compared to regular plastics, starch-based products exhibit some disadvantages mainly due to the highly hydrophilic nature of starch. Usually, strong hydrogen bonds hold the starch chain together, causing starch granules not to dissolve in cold water. This hydrophilic nature of starch causes low water stability and high sensitivity to moisture, which limits the development of starch-based materials. The properties of films produced from starch showed rigidity and reduced flexibility of the films. Thus, an addition of antioxidant to the packaging starch-based can improve the overall protection toward the products. Starch packaging provides moderate barrier to the oxidation, solubility, and water vapor permeability. The addition of antioxidant is needed to enhance the quality of the packaging. High number of additives can be added to the matrix, to improve the characteristics of the produced films. The final film obtained will be improved in the mechanical properties, and deterrent features.